THE RISE AND FALL OF UNIVERSAL BANKING: UPS AND DOWNS OF A SAMPLE OF LARGE AND COMPLEX FINANCIAL INSTITUTIONS SINCE THE LATE ‘90s - MASCIANTONIO, Sergio; TISENO, Andrea (Journal of Advanced Studies in Finance; Vol 4 No 1 (2013): JASF Volume IV Issue 1(7) Summer 2013, 2013)
We document the development of the major international banks since the late 1990s, analyzing balance-sheet data for 27 large and complex financial institutions. We argue that the balance-sheet expansion and business line diversification have paved the way for the rise of the universal banking model. This model, apparently sound and efficient in the run-up to the crisis, revealed all its shortcomings when the crisis erupted. European banks displayed greater fragilities in their business models. This changed financial and regulatory landscape that followed has challenged this model further. Many have proposed remedies to the global financial crisis and appear to consider returning to a narrower model for the banking activity.